Capillary‐Force‐Assisted Optical Tuning of Coupled Plasmons - Ding, Tao (Adv Mater, 2015)
An ultrathin (few nanometer) polymer spacer layer is softened by local optical heating and restructured by strong capillary forces, which increase the gap between the plasmonic metal components. This results in a continuous blue‐shift of the coupled plasmon from near infrared to visible with a tuning range of >150 nm that can be tightly controlled by adjusting either irradiation time or power. [Image: see text]